2000
DOI: 10.1177/172460080001500122
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Estrogen Receptor-Beta mRNA in Breast Cancer Using RT-PCR

Abstract: The estrogen receptor (ER) is the most useful marker currently available for breast cancer, being used both to predict response to therapy and assess prognosis. Recently, a new form of the ER, known as ER-beta, was identified. In this preliminary study we show that ER-beta mRNA was expressed less frequently in breast cancers than ER-alpha. ER-alpha but not ER-beta levels correlated with ER protein as determined by ELISA. We conclude that ER-beta is expressed in approximately 50% of breast cancers but it does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The reason for the different mitogenic effects exerted by E2 in colon cancer and breast cancer cells may reside in the expression of different estrogen receptors in the two cell lines. In this regard, we demonstrated that HT29 colonocytes express mainly ER , supporting previous observations (Arai et al 2000), whereas MCF-7 cells express mainly ER , as in previously reported findings (Cullen et al 2000). Further, ER and ER have different roles in the transcription regulation of various genes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The reason for the different mitogenic effects exerted by E2 in colon cancer and breast cancer cells may reside in the expression of different estrogen receptors in the two cell lines. In this regard, we demonstrated that HT29 colonocytes express mainly ER , supporting previous observations (Arai et al 2000), whereas MCF-7 cells express mainly ER , as in previously reported findings (Cullen et al 2000). Further, ER and ER have different roles in the transcription regulation of various genes.…”
Section: Discussionsupporting
confidence: 79%
“…In support of these hypotheses, different responses to AP1-activation sites exerted by ER and ER have been described by Paech et al (1997). Moreover, gene expression of ER in colorectal mucosa has been described (Arai et al 2000, Campbell-Thompson et al 2001), but ER is detected at very low levels in breast cancer tissues, according to our and others findings (Cullen et al 2000). These observations led us to suggest a functional implication for ER in estrogen's mediation of VDR expression in colonic cells.…”
Section: Discussionsupporting
confidence: 63%
“…In general, both receptors display similar ligand-binding profiles, but phytoestrogens like genistein and coumestrol induce receptor-dependent transcription stronger with ER␤ than with ER␣ [8,9]. Furthermore, the tissue distribution of ER␣ and ER␤ also differs substantially [8,10]. ER␤ is very important in the bone, urogenital tract, cardiovascular system, central nervous system and the developing brain [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…In 1996 it became evident that one major player in the story, the second ER, ERβ, had gone unnoticed (Kuiper et al 1996) and that its presence may well have some bearing on the development and treatment of hormone-dependent cancers. ERβ is highly expressed in the prostate (Kuiper et al 1996) and is expressed together with ERα in both normal and malignant breasts (Dotzlaw et al 1997, Vladusic et al 1998, Fuqua et al 1999, Speirs et al 1999, Cullen et al 2000, Iwao et al 2000, Jarvinen et al 2000, Speirs & Kerin 2000, Omoto et al 2001, Roger et al 2001. It is, therefore, not surprising that a great deal of interest is focused on the role of ERβ in normal and malignant growth of these two organs.…”
Section: Introductionmentioning
confidence: 99%